Genetically modified bacteriophages. Issue 4 (24th February 2016) - Sagona, Antonia P.; Grigonyte, Aurelija M.; MacDonald, Paul R.; Jaramillo, Alfonso
Abstract : Applications of genetically modified bacteriophages. Abstract : Phages or bacteriophages, viruses that infect and replicate inside bacteria, are the most abundant microorganisms on earth. The realization that antibiotic resistance poses a substantial risk to the world's health and global economy is revitalizing phage therapy as a potential solution. The increasing ease by which phage genomes can be modified, owing to the influx of new technologies, has led to an expansion of their natural capabilities, and a reduced dependence on phage isolation from environmental sources. This review will discuss the way synthetic biology has accelerated the construction of genetically modified phages and will describe the wide range of their applications. It will further provide insight into the societal and economic benefits that derive from the use of recombinant phages in various sectors, from health to biodetection, biocontrol and the food industry.